Exploring the Association Between Resilience and Quality of Life Among Glaucoma Patients: Sleep Disturbance as a Mediating Factor - Peng, Qinqi; Qu, Bo; Sznajder, Kristin K.; Chen, Qiongli; Fu, Jiahui; He, Shan; Yang, Xiaoshi (Frontiers in Medicine, 2022)
Background: Patients with glaucoma may experience many symptoms such as blindness, which seriously affect their quality of life (QoL). Resilience is playing a vital role in enhancing the QoL and well-being of patients with chronic diseases. In addition, sleep disturbance is common in patients with glaucoma, leading to a decline in their QoL. However, there is a dearth of research on whether sleep disturbance plays a mediating role between resilience and QoL among glaucoma patients. Objective: The aim of this study is to explore the role of sleep disturbance in the relationship between resilience and QoL among glaucoma patients. Methods: From July to December 2019, a cross-sectional survey was conducted on 215 glaucoma patients in an ophthalmic hospital in Liaoning Province. Hierarchical multiple regression (HMR) analyses and structural equation modeling (SEM) were conducted to examine the factors related to QoL and to test the hypothesis that sleep disturbance mediates the relationship between resilience and QoL among glaucoma patients. Results: The average QoL score among glaucoma patients was 43.85±14.97 as reported by the Glaucoma Quality of Life-15 (GQL-15) scale, where a higher score indicating a poorer QoL. Resilience was found to be linked with a lower QoL score (P<0.01), while sleep disturbance was associated with a higher QoL score (P<0.01). When sleep disturbance was included in the model as partial mediator, the path coefficients for the association between resilience and QoL score was significantly decreased (a*b=-0.1, BCa95% CI: -0.154 -0.045). Conclusion: Findings of this study reflected that QoL among glaucoma patients in China was poor. Resilience was found to be an important positive factor, which could result in the improvement of QoL. Furthermore, sleep disturbance mediated the relationship between resilience and QoL among patients with glaucoma, thereby reducing the positive impact of resilience on QoL in glaucoma patients. Efforts to improve QoL among glaucoma patients may benefit from interventions that enhance the levels of resilience and promote healthy sleep.